Strategies to minimize the risk of cost overrun in construction building project during pre-contract stage / Ling Kah Gah - Ling , Kah Gah (2024)
Construction projects are prone to cost overruns, which can significantly impact project success and profitability. This study aims to establish a reference of workable strategies for stakeholders such as client, project sponsor, contractor, quantity surveyors, etc., during pre-contract stage to minimize the risk of cost overrun in construction building projects in Selangor, Malaysia. Although cost overruns can occur at any stage of a construction project, the pre-contract stage is critical as it sets the foundation for the entire project. As the saying goes, prevention is better than cure. It is crucial to identify the potential cost overrun before it becomes an uncontrolled situation. This paper aims to identify the factors during pre-contract stage that impacted cost overrun in construction building projects and evaluate their impacts. This paper also evaluates the impact of the strategies during the pre-contract stage to reduce the likelihood of cost overrun in construction building projects. The study involves a literature review of academic and draws on data from experienced practitioners, including developers, contractors and quantity surveyors, on previous construction building projects and utilizes quantitative research method. The top five factors related to pre-contract stage are Inflation, Inaccurate Estimation, Wrong Planning and Scheduling, Insufficient Contractor Experience and Inappropriate Managerial Skills. While the top three strategies to be used during pre-contract stage are Selection of contractors takes account of expertise, Pre-contract cost control, and Proper project activities planning. Ultimately, the findings of this research paper could benefit the construction industry by helping to improve project success and profitability through the prevention of cost overruns during the pre-contract stage.